A virtual potential field based coverage algorithm for directional networks - Zhao Jing; Zeng Jian-Chao (2009 Chinese Control and Decision Conference, 2009)
In order to increase coverage ratio of the directional networks by forcing sensors to turn from overlapping regions to coverage holes after random deployment, we introduce the force model of virtual potential fields and present a virtual potential field based coverage algorithm for directional networks. By sensors' turning under the ldquovirtual repulsive forcesrdquo caused by neighboring sensors and ldquovirtual attractive forcesrdquo caused by uncovered regions of the probable sense regions, coverage holes are eliminated quickly and sensors are more uniformly distributed, so the radio of directional networks is enhanced obviously. A set of simulation results are performed to demonstrate the effectiveness of the proposed algorithm.